ASSESSMENT OF COMPUTATIONAL THINKING: SEBUAH KAJIAN LITERATUR SISTEMATIS - Fanny Rahmatina Rahim; Ari Widodo; Yusi Riksa Yustiana; Minsu Ha (STKIP Pesisir Selatan, 2023)
The main objective of this study was to conduct a systematic literature review of the evaluation of computational thinking skills. The research method utilized was a comprehensive search of various databases through Google Scholar using the keyword